Crystal and magnetic structures of hexagonal YMnO3. Issue 6 (26th February 2016) - Howard, Christopher J.; Campbell, Branton J.; Stokes, Harold T.; Carpenter, Michael A.; Thomson, Richard I.
Abstract : The available data on the structural and magnetic transitions in multiferroic hexagonal YMnO3 have been reviewed, first making use of the computer programs from the group theoretical ISOTROPY software suite to list possible crystal and magnetic structures, then taking into account the capability of neutron diffraction and other physical methods to distinguish them. This leads to a clear view of the transformation sequence, as follows. Hexagonal YMnO3 is paraelectric in P 63 / mmc at elevated temperatures, and undergoes a single structural transition on cooling through 1250 K to a ferrielectric phase in P 63 cm that is retained through room temperature. At a much lower temperature, 70 K, there is a magnetic transition from paramagnetic to a triangular antiferromagnetic arrangement, most likely with symmetry P 63 ′ cm ′. Comment is made on the unusual coupling of ferroelectric and magnetic domains reported to occur in this material, as well as on the so‐called `giant magneto‐elastic' effect.